Performance testing framework for smart grid communication network - Quang D.N.; See O.H.; Chee L.L.; Xuen C.Y.; Karuppiah S. (Institute of Physics Publishing, 2023)
Smart grid communication network is comprised of different communication mediums and technologies. Performance evaluation is one of the main concerns in smart grid communication system. In any smart grid communication implementation, to determine the performance factor of the network, a testing of an end-to-end process flow is required. Therefore, an effective and coordinated testing procedure plays a crucial role in evaluating the performance of smart grid communications. In this paper, a testing framework is proposed as a guideline to analyze and assess the performance of smart grid communication network. Published under licence by IOP Publishing Ltd.